Critical Study of Rita Wahyu’s Interpretation of Matthew 1:20 - Is Jesus Christ the Holy Spirit? - Harman Ziduhu Laia; Ponco Mujiono Basuki; Daniel Ari Wibowo (Theological Journal Kerugma, 2023)
An article titled “Yesus dan Roh Kudus” written by Rita Wahyu and published on the website “Sarapan Pagi Biblikal” became highly controversial in 2021, particularly regarding her interpretation of the text in Matthew 1:20. The article contains elements of Modalism, Modalistic Monarchianism, or Sabellianism, which teach about the Oneness of God, meaning that God has one nature and one person with three names: the Father, the Son, and the Holy Spirit. Rita emphasizes her thesis on the preposition ἐκ in the text, which she believes should be interpreted as “of” in English, indicating that the child in Mary’s womb is the Holy Spirit. However, research on the preposition ἐκ in Matthew 1:20 using exegetical methods based on Biblical grammatical laws shows that Rita’s interpretation lacks a basis that can be sustained exegetically. Her interpretation of the preposition is eisegesis, not exegesis. From an exegetical standpoint, the preposition ἐκ in the text indicates the source or origin of the child; the cause or agent of Mary’s pregnancy; and/or the giver of the seed of the baby in Mary’s womb, namely the Holy Spirit.